DO-DAT: A MATLAB toolbox for design & analysis of disturbance observer. Issue 25 (2018) - Chang, Hamin; Kim, Hyuntae; Park, Gyunghoon; Shim, Hyungbo
Abstract: Although the disturbance observer (DOB)-based controller has been extensively applied and various theoretical results on the DOB have been presented, the exclusive, user-friendly, and unified tool for the computer-aided design of DOB has not been developed yet. In this paper, the MATLAB toolbox DO-DAT ( Disturbance Observer - Design & Analysis Toolbox ) is introduced. Particularly, we explain the way of using the toolbox and present the applications of main functions in terms of the stabilization of the system and the time-domain performance analysis.